1970
DOI: 10.1172/jci106316
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of excessive purine biosynthesis in hypoxanthine-guanine phosphoribosyltransferase deficiency

Abstract: A B S T R A C T Certain gouty subjects with excessive de novo purine synthesis are deficient in hypoxanthineguanine phosphoribosyltransferase (HG-PRTase [EC 2.4.2.8]). The mechanism of accelerated uric acid formation in these patients was explored by measuring the incorporation of glycine-14C into various urinary purine bases of normal and enzyme-deficient subjects during treatment with the xanthine oxidase inhibitor, allopurinol.In the presence of normal HG-PRTase activity, allopurinol reduced purine biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
5

Year Published

1970
1970
1976
1976

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 26 publications
2
23
1
5
Order By: Relevance
“…This virtually complete absence of hypoxanthine-guanine phosphoribosyltransferase in patients with the Lesch-Nyhan syndrome has distinguished them from a group of subjects with a partial deficiency of hypoxanthine-guanine phosphoribosyltransferase (0.03 to 30% of normal) who have gout and hyperuricemia but are without serious neurologic disease (5,14). In the present study, we have found very low but reproducibly detectable levels of hypoxanthine-guanine phosphoribosyltransferase activity in erythrocytes of patients with the Lesch-Nyhan syndrome as have other investigators (15,16). However, the levels of hypoxanthine-guanine phosphoribosyltransferase activity in hemolysates from patients with the Lesch-Nyhan syndrome are still much lower than observed in most patients with gout who have the "partial" enzyme defect.…”
Section: Discussionsupporting
confidence: 49%
“…This virtually complete absence of hypoxanthine-guanine phosphoribosyltransferase in patients with the Lesch-Nyhan syndrome has distinguished them from a group of subjects with a partial deficiency of hypoxanthine-guanine phosphoribosyltransferase (0.03 to 30% of normal) who have gout and hyperuricemia but are without serious neurologic disease (5,14). In the present study, we have found very low but reproducibly detectable levels of hypoxanthine-guanine phosphoribosyltransferase activity in erythrocytes of patients with the Lesch-Nyhan syndrome as have other investigators (15,16). However, the levels of hypoxanthine-guanine phosphoribosyltransferase activity in hemolysates from patients with the Lesch-Nyhan syndrome are still much lower than observed in most patients with gout who have the "partial" enzyme defect.…”
Section: Discussionsupporting
confidence: 49%
“…2). Although levels of activity ranging from 0.2 to 5% of normal have recently been reported in several other patients with the classical syndrome, it is not clear whether the values observed are significantly above background in these particular studies or whether these also represent mutant forms of the enzyme with altered kinetic properties [49,65]. Despite the absence of detectable enzyme activity in hemolysates from most patients with this disease, all examined so far appear to have a protein which exhibits cross reactivity (CRM+) with an antibody to the normal enzyme [2].…”
Section: Enzyme Dejectmentioning
confidence: 77%
“…After the initial description of the enzyme defect, several investigators noted low levels of HGPRT activity in hemolysate from patients with this syndrome (2,3) while most found HGPRT activity undetectable (4)(5)(6). More recently we have noted a wide range of HGPRT activity over time in the same patient suggesting that environmental factors might partly account for this discrepancy.…”
Section: Introductionmentioning
confidence: 77%